Captured on the high seas - Hering, Marianne; Sanders, Nancy I.; Hohn, David, 1974- (Carol Stream, Illinois : Tyndale House Publishers, Inc., 2014)
When the Imagination Station sends time-traveling cousins Patrick and Beth to a ship that is captured by the British during the Revolutionary War, they are befriended by James Forten, a free Black of Philadelphia, and help save the life of an imprisoned boy dying of scurvy. Includes a secret word puzzle.
"Focus on the Family, Adventures in Odyssey."
Ages 7 and up.
Flesch-Kincaid grade level: 2.3.
Keywords: Forten, James, -- 1766-1842 -- Juvenile fiction; Space and time -- Juvenile fiction; Seafaring life -- Juvenile fiction; Prisoners -- Juvenile fiction; African Americans -- Juvenile fiction; Cousins -- Juvenile fiction; Christian life -- Juvenile fiction; United States -- History -- Revolution, 1775-1783 -- Juvenile fiction